Football's cash crisis - McQuillan, Stephen; BBC Active (Firm) ([Frenchs Forest, NSW : BBC Active, 2003)
Football is the richest, and arguably the most popular, sport in the world. But somehow, football clubs never seems to make any money. The Premier League is the richest league in the world, but why is Manchester United, of all major British clubs, the only one to be successful in consistently reporting profits? This special investigation seeks to find out why, in a game awash with money, hardly any club appears to make a profit.
Title from container
DVD format
Keywords: Football -- Economic aspects; Football